Computational intelligence for privacy and security - Elizondo, David A.; Marti´nez-Balleste´, Antoni; Solanas, Agusti (Berlin, Germany : Springer, 2012)
This book collects papers on computational intelligence for privacy and security. The majority are extended versions of works presented at the special session on Computational Intelligence for Privacy and Security of IJCNN-2010
1. Computational intelligence for privacy and security: introduction -- 2. An introduction to the use of neural networks for network intrusion detection -- 3. Evolutionary computation in computer security and forensics: an overview -- 4. Application of fuzzy logic in computer security and forensics -- 5. A topological study of chaotic iterations application to hash functions -- 6. SOM-based techniques towards hierarchical visualisation of network forensics traffic data -- 7. The application of evolutionary heuristics for solving soft security issues in MANETs -- 8. Mixing genetic algorithms and V-MDAV to protect microdata -- 9. Breaching privacy using data mining: removing noise from perturbed data -- 10. Feature selection of hand biometrical traits based on computation intelligence techniques -- 11. Building visual surveillance systems with neural networks -- 12. Advances in spam filtering techniques -- 13. Computational intelligent techniques and similarity measures for malware classification -- Intelligence techniques in computer security and forensics: at the boundaries of ethics and law
Includes bibliographical references and index
Keywords: Computational intelligence; Computer security